Pengembangan Media Pembelajaran Fisika Berbasis Web Menggunakan Google Sites Pada Materi Gelombang Bunyi - Ike Ismawati; Nila Mutia; Nurhikmah Fitriani; Salma Masturoh (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Distance learning used in physics teaching and learning activities is indeed difficult to apply properly, this is caused by the many formulas and theories that must be explained well and in detail and the difficulty of explaining to students so that students are not able to understand concepts, materials and theories properly. good. Based on the background described previously, the purpose of this study is to test the feasibility of web-based physics learning media using google sites on sound wave material in helping students to learn easily and independently during distance learning. Learning media using Google sites aims to help students learn physics independently, especially in learning physics with sound wave material. In this study, research and development (R&D) methods were used. Website-based learning media developed using Google Sites on the subject of Sound Waves received an average validation score of 50.50% by media experts and 63.50% by material experts. Both the average score results by media experts and material experts are included in the